Banks’ Strategies to Face Fintechs’ Attacks - Dedy Ihsan; Wahyu Murti; Sri Sungkowati (Sharia Oikonomia Law Journal, 2024)
Globalization has changed the playing field within industries, which were traditionally limited by size, country of origin, industry type, and past success. Now, those boundaries have become blurred and no longer clearly defined. Internet connectivity and technology have changed the face of businesses. These changes will always continue on an ongoing basis. For example, fintech (startups) that used to serve only one business segment have started to enter the banking industry, through online lending or peer to peer lending (P2P lending), products of savings, payment systems, and pay later. The latter is like a credit card in banking. Startups have become a very strong-new competitor for banks. Instead, their loan impressively grows with low non-performing loans (NPLs). Therefore, banks must be aware of this competitive situation. Banks should no longer use the old ways to compete, but should find and do new ways. For this reason, this paper is prepared to provide answers on how banks should respond, so that the competitive pressure from fintech can be carefully anticipated.